Formulasi Sediaan Lip Balm Ekstrak Etanol 96% Daun Jambu Air - Rahma, Fitrotur; Suproborni, Arum; Kusumawati, Desi (Pharmed: Journal of Pharmaceutical Science and Medical Research, 2026)
The guava plant can be utilized as an antioxidant agent, (Syzygium aqueum (Burm.f.) Alston.) from Malaysia and Indonesia. Guava leaves (Syzygium aqueum (Burm.f.) Alston), stores total flavonoids of no less than 0.07% and 1.65% in the viscous extract of guava leaves. The purpose of this study is to find out the most optimal formula for lip balm preparations that contain 96% rtanol extract of guava leaves as a natural antioxidant. Guava leaves were extracted by the recessation method in 96% ethanol solvent, phytochemical screening of guava leaf extract, ethanol-free test, optimization of lip balm preparations, and then evaluation. The results of the study obtained positive guava leaf extract containing flavonoid compounds, saponins, and tannins. The optimization of lip balm preparations was best produced in the 3rd optimization, the results of the evaluation of lip balm preparations had an average pH of 5.5 to 6.3, the melting temperature test was 54.3-65.3°C, the organoleptis of the preparation was stable during storage and homogeneous but experienced aroma changes in F1-F3, the highest preference test at F2 with an average rating of 3.3. Guava leaf extract has met quality requirements and can be formulated as an active ingredient in lip balm preparations.